Digital Marketing And Visual Content Design Determine Industrial Automation Brand Awareness: Pemasaran Digital Dan Desain Konten Visual Menentukan Kesadaran Merek Otomasi Industri - Marcello Dicaprio Putra Agung; Istian Kriya Almanfaluti (International Consortium of Education and Culture Research Studies, 2024)
General Background The rapid evolution of internet technologies transitions modern business operations from traditional methods to interactive online commercial strategies. Specific Background PT Mitsol Teknik Indonesia utilizes social media platforms and graphic software to promote technical equipment visually. Knowledge Gap Despite widespread social media adoption, the specific creative workflows and communication strategies required to market heavy equipment on consumer platforms remain underexplored. Aims This study investigates the applied online promotional strategies and the conceptualization process for generating attractive promotional materials. Results Qualitative descriptive analysis indicates that a structured workflow encompassing ideation, creation, evaluation, revision, and implementation successfully produces engaging publications. Furthermore, specific compositional choices, including bold typography, high-contrast color palettes like red and black, clear product imagery, and prominent corporate logos, consistently communicate technical reliability and professionalism. Novelty This research maps the exact compositional elements and iterative creative cycles necessary to translate complex technical specifications into accessible social media publications. Implications Companies must adopt structured creative workflows and precise branding parameters to build product recognition and overcome internal preference discrepancies in competitive online markets. Highlights: Structured creative workflows involving continuous evaluation cycles successfully produce engaging promotional materials. Bold typography combined with high-contrast color palettes consistently communicates technical reliability. Prominent corporate logos and clear machinery imagery establish professional credibility online. Keywords: Social Media Promotion, Graphic Composition, Corporate Identity, Iterative Workflow, Online Presence